De l’ « arrière-pays » au « vrai lieu » : le discours philosophique d’Yves Bonnefoy entre poésie et ontologie - Simona POLLICINO (Revue Roumaine d’Etudes Francophones, 2020)
Yves Bonnefoy’s reflection is not exempted from philosophical concerns, insofar as the French poet bases his poetic experience on an existential quest in this world, by considering his poetic collections as the steps of his search for the original meaning. The dialogue between conceptual thought and the immediate relationship of the human to the world on which Bonnefoy is questioning, leads to the choice of the presence of things on earth, opposing both abstract thought and materialism pushed to its limit. The purpose of this article is to analyse the poet’s vocabulary, focusing on the translator’s effort to keep Bonnefoy’s precision, clarity and “transparency”, even in textual passages where his reasoning is close to philosophical discourse.